Desain Silabus Bahasa Inggris Bagi Mahasiswa Jurusan Analis Kesehatan Poltekkes Kemenkes Kendari - Aswiro Hasan (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2019)
In preparing students for global professional communication, it is crucial to conduct an analysis related to teaching material, methods and context in which English are used. This study aims to design syllabi and teaching materials based on student needs. This research is a type of descriptive research. More accurate information about student needs is obtained through the provision of questionnaires and semi-structured interviews to students, alumni, and lecturers. Data were analyzed using quantitative and qualitative methods. The findings of this study reveal the need to establish learning that focuses on the target context of the Medical laboratory technologist either for academic or professional development. The contents of the syllabus needed by students are a series of aspects of language skills namely reading and speaking provided with topics of Medical laboratory and grammar that are appropriate to the context and presented in a series of varied learning activities that can provide convenience in the process of language acquisition in the classroom.